THE STUDY OF BOURDIEU’S SYMBOLIC VIOLENCE IN ALEX URBAN’S “THE KINGFISHER SECRET” - Zainul Arifin (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2021)
This study looks at symbolic violence in Alex Urban's novel The Kingfisher Secret. In Alex Urban's work The Kingfisher Secret, the author investigates the emergence of symbolic violence and analyzes Bourdieu's capital and habitus. To assist the understanding of symbolic violence, this research employs Pierre Bourdieu's symbolic violence idea, as well as habitus, field, and capital theory. This study employs Wellek and Warren's extrinsic method, in which literary material is examined from a social perspective. The author employs a descriptive qualitative technique to locate symbolic violence. The findings demonstrate that in Alex Urban's work The Kingfisher Secrets, symbolic violence is portrayed by offering a present (gift exchange), expressing compassion, delivering an order (indirect command), and respectfully declining. The habitus is brutally capitalistic, rationalizing any means and aspirations to improve one's life and circumstances. The agency uses symbolic violence to achieve its goals and gain dominance.